Pro-poor growth in Indonesia: Challenging the pessimism of Myrdal's Asian Drama - Charles Peter Timmer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This chapter addresses the unrelenting pessimism in Asian Drama about Indonesia's development prospects. This pessimism was based on two key realities: the poor level of governance demonstrated by the Sukarno regime (partly a heritage of Dutch colonial policies) and the extreme poverty witnessed in rural areas. Using historical and modern data on the Indonesian economy, the chapter explains the policy approach that resulted in three decades of rapid, pro-poor growth during the Suharto regime. The Asian financial crisis in 1998 caused the Suharto regime to fall and introduced democratically elected governments. After a decade of stagnation, economic growth returned to the rapid rate seen during the first three decades of the Suharto regime, but it is no longer pro-poor.
Keywords: B25; I32; N55; O53; 330; governance; Indonesia; pessimism; poverty; pro-poor growth